Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst